Calculating the iodine value for Italian heavy pig subcutaneous adipose tissue from fatty acid methyl ester profiles. (December 2016) - Lo Fiego, Domenico Pietro; Minelli, Giovanna; Volpelli, Luisa Antonella; Ulrici, Alessandro; Macchioni, Paolo
Abstract: In this work, different equations were compared as for their effectiveness in predicting the iodine value (IV), based on fatty acid (FA) composition of subcutaneous adipose tissue of Italian heavy pigs. In particular, six equations were tested: AOCS (1); modified AOCS (2), including all unsaturated FA (UFA); regression models obtained using the stepwise regression procedure as variable selection method, calculated considering only UFA (3) or all the FA (4); regression models obtained using the backward elimination procedure, calculated considering only UFA (5) or all the FA (6). The comparison of the equations performance, estimated using an external test set, showed that the use of regression models led to significant enhancements of prediction accuracy with respect to the AOCS equations. Using both equations 4 and 6, the average paired differences between experimental and predicted IV values were not statistically significant. Therefore, it is possible to use these equations for IV estimation of the subcutaneous adipose tissue of Italian heavy pigs. Highlights: Iodine value determination of pig fat is time consuming and has negative environmental impact. Iodine value of heavy pig fat can be estimated from fatty acid composition of lipids. AOCS Cd 1c-85 equation is frequently used, but it tends to underestimate iodine value. To improve predictive performance, different regression models were tested. Regression models showed better predictive performances than AOCS Cd 1c-85 equation.